Characterization of an Acute Rodent Osteomyelitis Infectious Model Using a Tibial Intramedullary Implant Inoculation - Assad, Michel; Downey, Anne Marie; Cluzel, Caroline; Trudel, Yannick; Doyle, Nancy; Authier, Simon (Frontiers in Bioengineering and Biotechnology, 2020)
Chronic osteomyelitis in presence of orthopedic implants is a condition observed in the field of biomaterials as it impairs early bone-implant contact, fixation and integration. In this study, a surgical intramedullary tibial insertion was performed using a titanium wire previously inoculated with Staphylococcus aureus in order to develop an osteomyelitis model in a clinically relevant long bone and in absence of any prophylactic treatment. As such, twenty-two male Sprague-Dawley rats received a sterile or inoculated intramedullary biomaterial with either 2×106 or 1×107 S. aureus colony forming units. Bacterial burden, inflammation, morphological changes, as well as newly formed bone tissues were evaluated for histopathology following a period of either eight or fifteen days of implantation. The implant inoculated in presence of the highest bacterial load was effective to produce significant periprosthetic infection observations in addition to hard and soft tissue inflammation consistent with the development of osteomyelitis. In contrast, neither the sterile nor the low-dose implant inoculation showed inflammation and clinical infection signs, but rather produced an expected bone remodeling and appropriate healing associated with biomaterial implantation. Complete health assessment is presented with histopathological periprosthetic results.